Psychometric approach to evaluate periodontal disease using Revised Illness Perception Questionnaire - A Rizwan Ali; Anjali Kapoor; Debopriya Chatterjee; Kompal Gautam; Aparna Choudhary; Rashi L Jain (Wolters Kluwer Medknow Publications, 2022)
Introduction: Illness perception is the cognitive representation of an illness, which determines how a person responds to it. The Revised Illness Perception Questionnaire (IPQ-R) assesses seven components of illness representation in various chronic diseases, but queries prevail about its factor structure. The study assesses the components of illness representation in patients with chronic periodontitis. Materials and Methods: A total of 625 voluntary, consecutive dental patients with a clinical diagnosis of periodontitis were recruited into the study. The Hindi version of IPQ-R was used, consisting of three parts-identity scale, structured scale, and perceived causes of the patient's ailment. Results: Of the 625 participants, 44.0% reported cyclical disease pattern, 30.4% said their disease was a mystery. Only 1.6% predicted it to remain throughout their life. A total of 44.0% of participants reported the disease to impact their day-to-day life severely. A significant difference was observed between males and females across seven components of IPQ-R. While 21.6% of participants attributed stress to be a major cause for their diseased state, 20.8% reported workload to be a major cause, but 42.4% attributed poor medical care in the past to be a major cause for their state. Conclusions: A sensible approach to treating a disease is to measure the patient's illness perception and target specific interventions accordingly. It would be cost-effective and break misconceptions about diseases in patients, ultimately providing them with better overall health and satisfaction.